Competências pedagógicas da preceptoria médica no Tocantins, sob o olhar do residente - Marinho, Ana Mackartney de Souza (Universidade Federal do Tocantins, 2018)
The relevance of the role of the preceptor in medical training is undeniable. And so it is necessary to make investments in their qualification. All this in the sense of improving their skills and attributes, especially pedagogical skills, aiming at improving the teaching-learning process and stimulating permanent education. The training of teachers and preceptors is decisive for modifying medical education in the country, and there is no way to train new professionals differently without competent and innovative teachers, whose professionals have a fundamental and indisputable role in the teaching-learning process of residents of RM. This study deals with the training of health preceptors and the importance of their qualification in the teaching-learning process of medicine. Given the complexity of the theme, we defined as general objective to evaluate the pedagogical competences of the Preceptory Course in Health in Tocantins and which, under the perception of medical residents, were more relevant and strategic in this context. To reach the proposed objectives, the technique used was the descriptive-exploratory research with qualitative approach method. Eight medical residency graduates from UFT - period from 2011 to 2016 - composed the sample of this study. The instrument of data collection was the semistructured interview, with content analysis method. It is hoped that the results of this study will contribute to the change and improvement of the quality of the Preceptoria em Saúde courses of UFT / ABEM, in the sense of introducing new methodologies and teaching didactics, both at the national level, and especially in the UFT and other medical teaching institutions in the region. The results obtained verified the relevance of the preceptor for medical training. It was concluded that the training and didactic training of the preceptor are of great relevance for him to succeed in his professional performance.